Primerjava delovanja roke pri dveh razlienih tehnikah strela v skoku pri rokometu - Pori, P.; Sibila, M. (Kinesiologia Slovenica, 2003)
The aim of this study is to identify differences in some basic kinematic parameters of arm activity between two different jump shot (JS) techniques used in handball. We compared the jump shot performed after the take-off from the leg opposite to the throwing hand (JS1) and the jump shot performed after the take-off from the throwing-side leg (JS2). Ten top-level male handball players executed six JS (three shots of each technique). Among all attempts performed, the two JS were chosen for each player (one for each technique) for further analysis. Two SVHS video cameras, operating at 25 frames per second, were used for data acquisition. Data processing was performed by APAS (Ariel Dynamics, California, USA). The basic statistical parameters for variables were computed and t-test for paired dependent samples and analysis of variance were used to assess statistical significance of the differences between the kinematic variables. The release ball velocity was significantly greater in JS1. In spite of the significant differences in times necessary for reaching the peak velocity of the wrist, elbow and shoulder of the throwing arm, there were no significant differences among the maximal velocities in the mentioned joints. At the final points of take-off and release, there were statistically significant differences between the angles of shoulder and hip axes in transversal plane. The differences were probably due to the take-off styles. The JS1 enabling better energy transfer from the distal to proximal body parts and better use of elastic muscle and ligament capacities in shooting from the opposite leg.